Habitat selection, diet and food availability of European Golden Plover Pluvialis apricaria chicks in Swedish Lapland. (3rd May 2017) - Machín, Paula; Fernández‐Elipe, Juan; Flinks, Heiner; Laso, Maite; Aguirre, José I.; Klaassen, Raymond H. G.
Abstract : Fennoscandian alpine tundra habitats support large numbers of breeding waders, but relatively little is known about their breeding ecology despite the fact that this habitat is threatened by climate change. We studied habitat selection, diet and prey availability of European (Eurasian) Golden Plover Pluvialis apricaria chicks at the Vindelfjällen Nature Reserve, Ammarnäs, Sweden. Information from 22 chicks tracked using radio‐transmitters was analysed. By analysing 149 faecal samples, four main prey taxa were identified, Coleoptera (40%), Bibionidae (31%), Hymenoptera (13%) and Tipulidae (10%). We found that chicks switched from feeding on Tipulidae to feeding on Bibionidae as they grew, and that this switch coincided with a shift from the use of the habitat where Tipulidae were abundant (alpine meadow/heathland) to the use of the habitat were Bibionidae were abundant (Willow shrub). Although chicks track food availability to some extent, the link between prey availability and habitat use was not perfect, indicating that additional factors other than food abundance, such as shelter from predators, determine habitat selection. Bibionidae are an important prey for Golden Plover chicks as it is the only prey group that has a late summer flush in abundance, in contrast to the general decline of total arthropod biomass during the chick‐rearing period. However, Bibionidae imagoes only occurred in 2011 and were virtually absent in 2013, which relates to the species' ecology with 2‐ to 5‐year cycles in mass occurrence. Extreme annual variation in an essential food source such as Bibionidae imagoes might have an important effect on the condition and survival of Golden Plover chicks, an important subject for future studies. The foraging conditions for Golden Plover chicks in Fennoscandia appear to be different to those in the UK, where the chicks rely mainly on a Tipulidae flush only.